MRNIP condensates promote DNA double-strand break sensing and end resection - Wang, Yun-Long; Zhao, Wan-Wen; Bai, Shao-Mei; Feng, Li-Li; Bie, Shu-Ying; Gong, Li; Wang, Fang; Wei, Ming-Biao; Feng, Wei-Xing; Pang, Xiao-Lin; Qin, Cao-Litao; Yin, Xin-Ke; et al. (Nature communications, 2022)
The rapid recognition of DNA double-strand breaks (DSBs) by the MRE11/RAD50/NBS1 (MRN) complex is critical for the initiation of DNA damage response and DSB end resection. Here, we show that MRN complex interacting protein (MRNIP) forms liquid-like condensates to promote homologous recombination-mediated DSB repair. The intrinsically disordered region is essential for MRNIP condensate formation. Mechanically, the MRN complex is compartmentalized and concentrated into MRNIP condensates in the nucleus. After DSB formation, MRNIP condensates move to the damaged DNA rapidly to accelerate the binding of DSB by the concentrated MRN complex, therefore inducing the autophosphorylation of ATM and subsequent activation of DNA damage response signaling. Meanwhile, MRNIP condensates-enhanced MRN complex loading further promotes DSB end resection. In addition, data from xenograft models and clinical samples confirm a correlation between MRNIP and radioresistance. Together, these results reveal an important role of MRNIP phase separation in DSB response and the MRN complex-mediated DSB end resection. The MRN complex is a critical sensor and processor of DNA double-strand breaks (DSBs). Here, the authors show that MRNIP forms liquid-like condensates to accelerate the MRN-mediated sensing and end resection of DSB, thereby promoting DSB repair.